Increasing the level of self-esteem in adolescent children through art therapy - T. S. Gordon (Publishing House of the State University of Management, 2020)
The possibility of using art therapy as a means of increasing the level of self-esteem in adolescent children has been proved theoretically. Psychological literature on the problem of therapeutic function of art therapy has been analysed. The levels of self-esteem, therapeutic possibilities of art therapy the possibility of using art therapy as an effective tool to increase the evaluation opinion of adolescents about the personal development of adolescent children have been highlighted. Actual creative activity, which includes art therapy, allows you to identify the relevant individual processes, as well as characteristic signs of personality development in the mental life of a teenager. An additional effect and guarantee of securing performance will be if a teenager after art therapy turns artistic activity into a hobby. The potential of this therapeutic area for self-esteem correction is the ability of teenagers to express their positive and negative emotions in an artistic form, solve internal conflicts, relieve anxiety, and much more.